Infection-Related Hospital Admissions After Prostate Biopsy in United States Men. (13th January 2017) - Evans, Richard; Loeb, Aram; Kaye, Keith S.; Cher, Michael L.; Martin, Emily T.
Abstract: Antibiotic prophylaxis during prostate biopsy is widespread; however, rates of postbiopsy infections have been rising. In an analysis of insurance claims data for 515045 prostate biopsies, 1.55% were hospitalized with infectious complications, with a mean total payment 14498.96. Infection was the second most common reason for 30-day hospital readmission.